Childhood Blindness - Ajaiyeoba Al. (Nigerian Journal of Paediatrics)
Summary: The results of a retrospective study of 119 children who attended the Eye Clinic, C'niversity College Hospital, Ibadan, with various eye complaints leading to blind ness in one or both eyes are presented. The leading causes of blindness in the present series included eye injuries which accounted for 33.6 percent, measles/keratitis associated with malnutrition in 28.6 percent, cataract in 6.7 percent and ocular infections in 6.7 percent of the cascs. Despite several past recommendations, including preventive and control measures on the condition, childhood blindness in Ibadan is as common now as it was some 25 years ago. In the present study, most of the causes of the blindness were preventable just as they were earlier reported from this same institution.